A Text Linguistic Defragmentation of Selected Health-Related Radio Advertisements in Nigeria - Agbeleoba, Samuel Oyeyemi (Advances in Social Sciences Research Journal, 2026)
This paper conducts a text linguistic defragmentation of selected health-related radio advertisements in Nigeria, employing De Beaugrande and Dressler's seven standards of textuality as the analytical framework. The study examines six representative advertisements broadcast in English, Nigerian Pidgin, and Yoruba, addressing malaria prevention, Lassa fever awareness, family planning, COVID-19 prevention, and maternal health. Through systematic analysis of cohesion, coherence, intentionality, acceptability, informativity, situationality, and intertextuality, the research reveals how linguistic choices strategically enhance message effectiveness across diverse audiences. The findings indicate that successful health advertisements in Nigeria employ multilingual strategies, culturally resonant metaphors, and context-specific appeals that align with the socio-linguistic realities of their target populations. This study fills a significant gap in the literature by applying a rigorous text-linguistic framework to radio health communication in Nigeria, offering evidence-based insights for practitioners and policymakers seeking to design more effective public health campaigns.